Effect of group cognitive behavioural therapy on psychological stress and blood glucose in people with type 2 diabetes mellitus: A community‐based cluster randomized controlled trial in China - Xu, Chunrong; Dong, Zongmei; Zhang, Pan; Chang, Guiqiu; Xiang, Quanyong; Zhang, Ming; Zhou, Jinyi; Qiao, Cheng; Yang, Qing; Qin, Yu; Lou, Peian (Diabetic medicine, 2021)
Objective To assess whether group cognitive behavioural therapy (GCBT) delivered by general practitioners reduces anxiety and depression and improves glycaemic levels in adults with type 2 diabetes mellitus. Methods We conducted a community‐based cluster randomized controlled trial in adults with type 2 diabetes mellitus from 48 communities in China. Participants received either GCBT plus usual care (UC) or UC only. General practitioners were trained in GCBT before intervention in the intervention group. The primary outcome was glycated haemoglobin (HbA1c) concentration. Outcome data were collected from all participants at baseline, 2 months, 6 months and 1 year. The secondary outcomes were depression (Patient Health Questionnaire‐9; PHQ‐9) and anxiety (General Anxiety Disorder questionnaire; GAD‐7). Results The GCBT group showed greater improvement in GAD‐7 and PHQ‐9 scores, respectively, than the UC group after 2 months post‐baseline (T = −6.46, p < 0.0001; T = −5.29, p < 0.001), 6 months (T = −4.58, p < 0.001; T = −4.37, p < 0.001) and 1 year post‐intervention (T = −3.91, p < 0.001; T = −3.57, p < 0.001). There was no difference in HbA1c values between the GCBT and UC groups at 2 months while the values were lower in the GCBT group at 6 months and 1 year (T = −6.83, p < 0.001; T = −4.93, p < 0.001, respectively). Subgroup analysis indicated a long‐term effect of GCBT only for mild and moderate anxiety and mild depression groups. Similarly, HbA1c values reduced only in the mild and moderate anxiety and the mild depression groups. Conclusions General practitioners can deliver GCBT interventions. GCBT plus UC is superior to UC for reducing mild/moderate anxiety and depression, and improving glycaemic levels. Trial registration Chinese clinical trials registration (ChiCTR‐IOP‐16008045).